1999
DOI: 10.1128/aac.43.5.1211
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Enhancement of Antibiotic Action on Escherichia coli Biofilms: an In Vivo Model

Abstract: Biofilm infections are a common complication of prosthetic devices in humans. Previous in vitro research has determined that low-frequency ultrasound combined with aminoglycoside antibiotics is an effective method of killing biofilms. We report the development of an in vivo model to determine if ultrasound enhances antibiotic action. Two 24-h-old Escherichia coli (ATCC 10798) biofilms grown on polyethylene disks were implanted subcutaneously on the backs of New Zealand White female rabbits, one on each side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…In vivo applications of this bioelectric process, termed``iontophoresis'', still have to be developed, but the process may be utilized for sterilization of tubing and instruments which can harbor bio®lms [48,67,68,70]. Finally, low-intensity ultrasound (500 kHz and 10 mW/cm 2 ) may alter bio®lms, and enhance the ecacy of drugs such as gentamicin on Pseudomonas aeruginosa [57].…”
Section: Bio®lm Formation and Prevention Of Infectionmentioning
confidence: 99%
“…In vivo applications of this bioelectric process, termed``iontophoresis'', still have to be developed, but the process may be utilized for sterilization of tubing and instruments which can harbor bio®lms [48,67,68,70]. Finally, low-intensity ultrasound (500 kHz and 10 mW/cm 2 ) may alter bio®lms, and enhance the ecacy of drugs such as gentamicin on Pseudomonas aeruginosa [57].…”
Section: Bio®lm Formation and Prevention Of Infectionmentioning
confidence: 99%
“…Whereas exposure to ultrasound alone caused no consi-derable difference in bacterial viability, in the presence of gentamicin, there was a substantial reduction in bacterial viability (the bioacoustic effect). Here, the ultrasound significantly reduced bacterial viability below that of nontreated biofilms without damage to the skin [67,68]. They hypothesized that stable cavitation or sonoporation might be involved in increasing the transport of antibiotics into the bacteria either by reducing the mass transfer boundary layer around the cells, or by altering the cell membrane, thus allowing the antibiotics to diffuse through newly formed membrane pores.…”
Section: Ultrasound Enhancement Of Antimicrobial Transportmentioning
confidence: 95%
“…Carmen et al [66] reported that S. epidermidis biofilms responded favorably to combinations of ultrasound and vancomycin at 48 hours of insonation. In addition, pulsed ultrasound enhances the killing of E. coli biofilms by aminoglycosides in a rabbit model with subcutaneously implanted polyethylene disks [67,68]. These authors applied low-frequency (28.48 kHz) and low-power density (300 mWcm -2 ) ultrasound treatment for 24 hours with and without systemic administration of gentamicin.…”
Section: Ultrasound Enhancement Of Antimicrobial Transportmentioning
confidence: 97%
“…A large body of in vitro and in vivo literature exists on enhanced uptake of unbound chemicals into mammalian cells [152,153], and, especially tumour cells [154][155][156][157][158], in the presence of ultrasound. Similarly, ultrasound potentiates the effect of antibiotics on bacteria in culture [159][160][161] and in animals [162,163]. Ultrasound has also been used for selective delivery of conjugated drugs to their targets, avoiding the harmful side effects.…”
Section: Targeted Chemotherapymentioning
confidence: 99%